An evaluation of New Zealand political party Websites. - Matthew Conway; Dan Dorner (Information Research: An International Electronic Journal)
In a very short time, Websites have become vital campaign and communication tools for political parties around the world. This study examines the effectiveness of the Websites of New Zealand political parties, focusing on the functions that the parties were performing online and on how effectively they were delivering these functions. The research was designed to provide a quantitative evaluation of party Websites and to allow for longitudinal comparisons and comparisons between countries. Using a coding scheme that measured 50 different criteria numerically, providing for objective evaluation and comparison, the study found that New Zealand political parties were not using the Internet effectively, mainly because most were using their Websites for information provision, yet were not providing the tools required to make this information as accessible as possible. The research also found that the major parties were using their Websites more effectively than the minor and non-parliamentary parties, but the most effective Website belonged to the Green Party.